Amnesty for Even the Worst Offenders - Jay Butler (Washington University Law Review, 2017)
In recent years, global policy makers have declared that heads of state must be held accountable through criminal prosecution for internationally wrongful acts. Scholars too have insisted that the international system’s embrace of accountability excludes or renders illegal the granting of amnesty. This Article argues that that position is too narrow and uses the ongoing conflict in Syria, as well as other contemporary examples, to examine some of consequences of the clamor for prosecution. The Article rejects the binary juxtaposition of amnesty and accountability in current international legal scholarship, and instead seeks to broaden the terms of the conversation by considering amnesty from the perspective of the Responsibility to Protect (R2P) principle. The Article suggests that viewing amnesty as a conflict resolution mechanism that may discharge R2P highlights important values and tradeoffs that the debate over amnesty and its relation to accountability has heretofore neglected.
Keywords: amnesty; international criminal law; human rights; responsibility to protect; R2P